Computational Modeling of NLRP3 Identifies Enhanced ATP Binding and Multimerization in Cryopyrin-Associated Periodic Syndromes - Samson, Jenny Mae; Ravindran Menon, Dinoop; Vaddi, Prasanna K.; Kalani Williams, Nazanin; Domenico, Joanne; Zhai, Zili; Backos, Donald S.; Fujita, Mayumi (Frontiers in Immunology, 2020)
Cyropyrin-associated periodic syndromes (CAPS) are clinically distinct syndromes that encompass a phenotypic spectrum yet are caused by alterations in the same gene, NLRP3. Many CAPS cases and other NLRP3-autoinflammatory diseases (NLRP3-AIDs) are directly attributed to protein-coding alterations in NLRP3 and the subsequent dysregulation of the NLRP3 inflammasome leading to IL-1β-mediated inflammatory states. Here, we used bioinformatics tools, computational modeling, and computational assessments to explore the proteomic consequences of NLRP3 mutations, which potentially drive NLRP3 inflammasome dysregulation. We analyzed 177 mutations derived from familial cold autoinflammatory syndrome (FCAS), Muckle-Wells Syndrome (MWS), and the non-hereditary chronic infantile neurologic cutaneous and articular syndrome, also known as neonatal-onset multisystem inflammatory disease (CINCA/NOMID), as well as other NLRP3-AIDs. We found an inverse relationship between clinical severity and the severity of predicted structure changes resulting from mutations in NLRP3. Bioinformatics tools and computational modeling revealed that NLRP3 mutations that are predicted to be structurally severely-disruptive localize around the ATP binding pocket and that specific proteo-structural changes to the ATP binding pocket lead to enhanced ATP binding affinity by altering hydrogen-bond and charge interactions. Furthermore, we demonstrated that NLRP3 mutations that are predicted to be structurally mildly- or moderately-disruptive affect protein-protein interactions, such as NLRP3-ASC binding and NLRP3-NLRP3 multimerization, enhancing inflammasome formation and complex stability. Taken together, we provide evidence that proteo-structural mechanisms can explain multiple mechanisms of inflammasome activation in NLRP3-AID.